Targeting CXCR1/CXCR2 receptor antagonism in malignant melanoma - Sharma, Bhawna (Expert Opin Ther Targets, 2010)
IMPORTANCE OF THE FIELD: The incidence of malignant melanoma is increasing throughout the world and is currently rising faster than any other cancer in men and second only to lung cancer in women. Current strategies focused on systemic therapy for treatment of have shown no effect on survival. Therefore there is a pressing need for developing novel targeted therapeutics. AREAS COVERED IN THIS REVIEW: Our goal is to provide an overview regarding targeting CXCR1/2 in malignant melanoma, the rationale behind these approaches and the future perspective. WHAT THE READER WILL GAIN: This review illustrates our current understanding of CXCR1/2 receptor in melanoma progression and metastasis. We describe approaches that are being developed to block CXCR1/2 activation, including low-molecular-weight antagonists, modified chemokines and antibodies directed against ligands and receptors. TAKE HOME MESSAGE: The chemokine receptors CXCR1 and CXCR2 and their ligands play an important role in the pathogenesis of malignant melanoma. Recent reports demonstrated that CXCR1 is constitutively expressed in all melanoma cases irrespective of stage and grade, however, CXCR2 expression was restricted to aggressive melanoma tumors,. Furthermore, modulation of CXCR1/2 expression and/or activity has been shown to regulate malignant melanoma growth, angiogenesis and metastasis, suggesting CXCR1/2 targeting as a novel therapeutic approach for malignant melanoma.